Detection of Liberibacter asiaticus causing Citrus Vein Phloem Degeneration from Siam Citrus leaves (Citrus nobilis var. microcarpa) in Singkawang City plantation, Pontianak, West Kalimantan - RAHMAWATI RAHMAWATI; ILIANA ILIANA; AGUS RACHMAT; LATIFFAH ZAKARIA; MUKARLINA MUKARLINA (Microbiology Indonesia, 2020)
The objective of the present study was to detect presence of pathogenic fastidious bacterium, Candidatus Liberibacter asiaticus using PCR from leaves of Siam citrus showing Citrus Vein Phloem Degeneration (CVPD) symptoms in Singkawang City plantation, Pontianak, West Kalimantan, Indonesia. Citrus leaf samples were collected based on visual observation of symptoms showing CVPD infection. Typical symptoms of CVPD include leaf yellowing (chlorosis), vein banding, leaves become stiff, thicker and smaller in size. The pathogenic bacterium, Candidatus Liberibacter asiaticus was detected using two specific primers, namely, OI1/ OI2c amplified 16S rRNA gene and A2/J5, amplified ribosomal protein gene of the rplKAJL-rpoBC operon (Î²-operon). PCR amplification detected the presence of 1100 bp band using OI1/ OI2c primers, and 703 bp band using A2/J5 primers from symptomatic Siam citrus leaves. PCR products were not detected from healthy plants serve as control. By using two sets of specific primers to amplify 16S rRNA gene and ribosomal protein gene, Candidatus Liberibacter asiaticus was detected in symptomatic Siam citrus leaves in Singkawang City, Pontianak, Indonesia. Detection of the bacterial pathogen causing CVPD is important to prevent spreading of the disease which could affect production of citrus fruits.